The influence of extracellular - originating signals on THEmTOR / mTORC1 signalling pathway to autophagy induction in HOSCC - Nerwich, Ari Nathan (My University, 2013)
Cell-extracellular matrix (ECM) detachment triggers a cell survival mechanism known as autophagy. A link between attachment and autophagy suggests a form of adhesion-based regulation, involving mechanotransduction of extracellular-originating signals to the cellular machinery controlling autophagy induction. This implies a role for integrin-linked kinase (ILK), which transmits mechanical stimuli to the mammalian target of rapamycin (mTOR) signalling pathway. Cells with a propensity for metastasis may negate these adhesive signals, inducing autophagy inappropriately. Metastasis is a hallmark of transformation frequently associated with human oesophageal squamous cell carcinoma (HOSCC). Additionally, hyperactive mTOR/mTORC1 signalling correlates increasingly with HOSCC. Therefore, the protein expression of significant signal transduction pathway intermediates was investigated in response to both soluble and ECM-originating stimuli. Measurements by SDS-PAGE and western-blotting coupled to semi-quantitative densitometry, during standard tissue culture conditions, revealed that HOSCC’s expressed moderate-to-high levels of mTOR, p-RPS6(Ser 235/236) and mATG-13; indicating elevated levels of autophagy induction despite aberrant signalling through mTOR/mTORC1. Additionally, an 80 kDa mTORβ isoform was identified in HOSCC cells with lower mTOR abundance, presumably to maintain aberrant mTORC1 signalling. A canonical role for the PI3K/PKB pathway was also identified; where autophagy induction accompanied diminished mTORC1 signalling in response to specific PI3K inhibition with LY294002 and serum withdrawal. However, autophagy induction varied in response to a dose-dependent decrease in mTORC1 signalling after exposure of HOSCC cells to rapamycin. Moreover, specific inhibition of p90RSK with BI-D1870, suggests that mTORC1 phosphorylates RPS6(Ser 235/236) in the absence of MAPK signals. Furthermore, ectopic ILK expression indicated an enhanced potential for adhesion-based signalling. Correspondingly, HOSCC cells commonly increased mTOR and p-RPS6(Ser 235/236) expression following growth on fibronectin or collagen. However, co-immunoprecipitation analysis revealed that signals transduction to mTOR precludes a direct interaction with ILK or FAK. Rather, ECM-modulation of mTOR occurs in a integrin-triggered, but PI3K-depedant manner; since specific inhibition of PI3K negated fibronectin-induced increases of mTOR concentration and RPS6(Ser 235/236) phosphorylation. Thus, these data strongly suggest mTOR is a target for adhesion-based signal transduction, where the ECM influences cell survival through mTORC1. Moreover, exploitation of autophagy induction post cell-ECM detachment in HOSCC may promote the survival of metastases during dissemination.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2012
Keywords: Squamous cell carcinoma.; Skin cancer.; Autophagic vacuoles.